マクマードキチ フキン ノ ケイソウ ショクセイ - 福島, 博; フクシマ, ヒロシ; FUKUSHIMA, Hiroshi (国立極地研究所, 1969)
P(論文) Thirteen taxa were identified, of which eight were Antarctic endemic species and five were cosmopolitan. In the first material in which dominant species could be found, Antarctic endemic Navicula muticopsis was dominant. Thus, it may be concluded that in the diatoms distributed around McMurdo Station an Antarctic endemic factor is stronger than a cosmopolitan factor. departmental bulletin paper